Black-Box Model, Identification Technique and Frequency Analysis for PEM Fuel Cell With Overshooted Transient Response - Raga, Carmen; Barrado, Andres; Lazaro, Antonio; Fernandez, Cristina; Valdivia, Virgilio; Quesada, Isabel; Gauchia, Lucia (IEEE transactions on power electronics, 2014)
Fuel cells are one of the most promising energy sources, especially for onboard applications. However, fuel cells present several drawbacks, such as slow dynamic response, load-dependent voltage, and unidirectional power flow, which cause an inappropriate vehicle operation. So, secondary energy sources and power converters must be implemented in order to satisfy fast changes in the current load and to store the energy delivered by the load if regenerative braking is intended. Taking into account the number and nature of the power converters, loads, secondary energy sources, and the possibilities for the control strategies, the design of a power distribution architecture based on fuel cells for transport applications is a complex task. In order to address these architectures, modeling and simulation design tools at system level are essential. This paper proposes a complete fuel cell black-box model which reproduces the behavior of a commercial fuel cell with overshooted transient response. The identification technique applied to parameterize the model components, based on manufacturer's datasheets and a test based on load steps, is explained thoroughly. In addition, if only the fuel cell frequency response and manufacturer's datasheet are available, an alternative parameterization methodology based on the fuel cell frequency response is presented. The fuel cell black-box model is validated experimentally using a commercial proton exchange membrane fuel cell. Two different parameterizations are carried out with the aim of verifying the robustness of both the fuel cell model and the proposed identification methodology.